Salt: Portuguese consumer’s perception and its occurrence in processed foods - Albuquerque, T.G. (2019)
Introduction: Salt consumption in Portugal (10.7 g/day) is almost the double than the recommended daily intake (5 g/day) (1). It is well documented that a high intake of salt is linked to several harmful effects on health, namely cardiovascular diseases. The main objectives of this study were: (i) to evaluate the perception of Portuguese consumers on the contribution of processed foods for salt intake and potential health impact; and (ii) to assess the salt content in 218 processed foods widely available in the market.